2006
DOI: 10.1152/ajpendo.00236.2005
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in liver, muscle, and adipose tissue insulin sensitivity in men with HIV infection and dyslipidemia

Abstract: In this study, a two-stage euglycemic hyperinsulinemic clamp, with infusion of stable isotopically labeled tracers, was used to evaluate insulin action in skeletal muscle, liver, and adipose tissue in HIV-infected men with dyslipidemia (HIV-DL; plasma triglyceride Ͼ250 mg/dl and HDL Ͻ45mg/dl; n ϭ 12), HIV-infected men without dyslipidemia (HIV w/o DL; n ϭ 12), and healthy men (n ϭ 6). Basal rates of glucose production (glucose R a), glucose disposal (glucose R d), and lipolysis (palmitate Ra) were similar betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 52 publications
2
48
0
Order By: Relevance
“…In agreement with others, we found that fasting FFAs and liver lipid content were elevated and positively correlated in HIVϩIGT subjects (11,13,35). The correlations between FFA levels, glucose, and leucine kinetics in HIVϩIGT subjects raise the possibility that elevated FFA flux and their byproducts can accumulate in insulinsensitive tissues and disrupt normal insulin signaling pathways.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with others, we found that fasting FFAs and liver lipid content were elevated and positively correlated in HIVϩIGT subjects (11,13,35). The correlations between FFA levels, glucose, and leucine kinetics in HIVϩIGT subjects raise the possibility that elevated FFA flux and their byproducts can accumulate in insulinsensitive tissues and disrupt normal insulin signaling pathways.…”
Section: Discussionsupporting
confidence: 92%
“…IGT was defined as fasting glucose 100 -126 mg/dl or glucose 140 -200 mg/dl 2 h after ingesting a 75-g glucose beverage (American Diabetes Association criteria). Glucose and fatty acid kinetics for 30 of these 47 subjects were reported previously in a study of men with HIV dyslipidemia (11).…”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…In situations of hypoadiponectinemia in humans, redistribution of fat in different depots or in other tissues determines the existence of low levels of adiponectin, especially when the fat is deposited in visceral depots, liver or muscle (32)(33)(34). Furthermore, we speculate that the lack of insulin stimulation observed in muscle from PPγ2KO-P mice could be related to alterations in WAT, and could also contribute to the higher degree of peripheral IR found in these animals.…”
Section: Acknowledgmentsmentioning
confidence: 86%